Employment Implications of India's Industrialization: Analysis in an Input Output Framework - Hazari, Bharat R.; Krishnamurty, J. (The Review of Economics and Statistics, 1970)
Bharat R. Hazari, J. Krishnamurty, Employment Implications of India's Industrialization: Analysis in an Input Output Framework, The Review of Economics and Statistics, Vol. 52, No. 2 (May, 1970), pp. 181-186